2011
DOI: 10.1017/s0954579411000083
|View full text |Cite
|
Sign up to set email alerts
|

Risky shifts: How the timing and course of mothers' depressive symptoms across the perinatal period shape their own and infant's stress response profiles

Abstract: We investigated the effects of timing and the course of maternal perinatal depressive symptoms on mother-infant hypothalamic-pituitary-adrenal (HPA) response profiles during an attachment stressor, as well as on within-dyad synchrony of stress profiles: coordination of HPA and sympathetic nervous system and infant-mother HPA attunement. Mothers (n = 86) completed the Center for Epidemiological Studies Depression Scale during pregnancy (Time 1 [T1]) and at 5 months (T2) and 18 months (T3) postnatal. At T3 mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
149
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 98 publications
(161 citation statements)
references
References 69 publications
(84 reference statements)
11
149
0
1
Order By: Relevance
“…Combined with earlier research showing matched phase coordination among non-depressed, but not depressed, women and their infants (Laurent et al, 2011), the current finding that women reporting more positive stress anticipation showed stronger cortisol-sAA coordination lends preliminary support to this idea. It may be that positive appraisals allowed active challenge reactions to more closely support threat reactions to the stressor.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Combined with earlier research showing matched phase coordination among non-depressed, but not depressed, women and their infants (Laurent et al, 2011), the current finding that women reporting more positive stress anticipation showed stronger cortisol-sAA coordination lends preliminary support to this idea. It may be that positive appraisals allowed active challenge reactions to more closely support threat reactions to the stressor.…”
Section: Discussionsupporting
confidence: 77%
“…A study testing both forward- and backward-lagged effects in an all-male sample yielded mixed evidence for positive vs. negative associations between cortisol and sAA (Engert et al, 2011). The only previous study of matched phase coordination as operationalized here found positive cortisol-sAA associations only among non-depressed women and their infants (Laurent et al, 2011). Given this and other evidence that discordance between HPA and ANS responses may signal mental health problems (Ali & Pruessner, 2012), a key task at this point is to determine how these systems are functionally related in real-life stress contexts and what predicts coordination vs. discordance.…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…Although all of our adoptees were adopted at a very young age, it still is possible that prenatal and perinatal problems set the stage for HPA-axis functioning (Gunnar & Fisher, 2006). This is consistent with evidence that the prenatal and perinatal periods are of importance for child development (e.g., Laurent, Ablow, & Measelle, 2011;Talge, Neal, & Glover, 2007). In our sample, the birthmothers of the adoptees may have been at a relatively high risk for depression, stress, malnutrition and other (maternity) problems.…”
Section: Discussionsupporting
confidence: 81%